سیرت نگاری میں ڈاکٹرمحمد یٰسین مظہر صدیقی کی تنقیدات(تصحیح ِروایات) کا تجزیاتی مطالعہ: An Analytical Study of Criticisms (about correction of narrations) of Dr. Yaseen Mazhar Siddiqui in Seerah Writing - Khalid, Iqra; Dr. Syeda Sadia (Seerat Studies, 2023)
Dr. Yaseen Mazhar Siddiqui, is a well-known seerah writer and historian. He wrote many books and articles in this respect. In his writings, he has exposed the prevailing wrong ideas and theories related to the Prophet's biography. There are many incidents and cases which are very famous and true in generally but Dr. Yaseen proved them wrong through his research. He presented his arguments regarding incidents which seem very difficult to ignore or deny, because those arguments are so universal and common sense that even a common man is forced to accept them. In this article we are presenting analytical study of some of these incidents theories.